Piezoelectric EMI Filter for Switched-Mode Power Supplies - Hubert, Florian; Dorsch, Philipp; Kübrich, Daniel; Dürbaum, Thomas; Rupitsch, Stefan (IEEE Transactions on Power Electronics, 2020)
We introduce a novel electromagnetic interference suppression method based on the piezoelectric effect for switch-mode power supplies (SMPSs). A piezoelectric interference-suppression component (PISC) generates a low-impedance propagation path for conducted emissions at its resonance frequency. This results in an attenuation of a discrete disturbance peak. Besides the resonance frequency, the PISC features capacitive behavior. Thus, PISCs can not only substitute regular capacitors (e.g., Y-capacitors), but also provide selective attenuation at discrete frequencies. Moreover, PISCs have the potential to reduce size, weight, and cost of SMPSs because the filter size can be reduced while still fulfilling electromagnetic interference regulations through the use of the PISC. We proof this concept by integrating the PISC in a flyback converter and investigate the attenuation of the common-mode disturbance. In addition, the influence of frequency shifts for the circuitry and the PISC is evaluated. In our measurements, the PISC suppresses a discrete disturbance peak at the switching frequency by 45 dB, which was found to be 17 dB better than the conventional approach. Furthermore, determining factors for a proper usage in SMPS, such as temperature dependence, safety ratings, etc., were examined, and an appropriate design procedure is given. Finally, typical application scenarios for PISCs are describe
Keywords: Flyback Converter; EMI Filter; Piezoelectric Effect; Interference-Suppression Capacitor